THE RELATIONSHIP OF FAMILY SUPPORT AND SELF ESTEEM WITH STUDENTS' ACADEMIC RESILIENCE AT SMK NEGERI 8 TIK JAYAPURA - Mathilda Monalisa Marbun; Suryani Hardjo; Salamiah Sari Dewi (RADJA PUBLIKA, 2024)
Academic Resilience: Many students currently, especially in Jayapura, have problems implementing learning services. Student academic resilience is certainly influenced by many factors. This research aims to analyze and determine the relationship between family support and self-esteem and students' academic resilience. This research is included in causal associative quantitative research. The sample for this research was 169 students at SMK Negeri 8 ICT Jayapura. Research data was collected using a research scale that was declared valid and reliable. The data analysis technique uses multiple linear regression analysis. The research results show that (1)There is a relationship between family support and academic resilience.From the results of statistical analysis, it was found that the rx1y correlation coefficient was 5.128with p < 0.05, this means that the level of family support is significantstudents' abilities will be able to increase or decrease students' academic resilience. (2)There is a relationship between self-esteem and students' academic resilience.From the results of statistical analysis, it was found that the correlation coefficient rx2y was 0.620 with p < 0.05, thus it can be concluded that whether or not a lot of self-esteem received by students will increase or decrease students' academic resilience. (3)There is a relationship between family support and self-esteem with students' academic resilience.From the results of statistical analysis it was found that the F reg coefficient = 13.829 with p < 0.05, and the correlation coefficient R = 0.593 with p < 0.05 and t table = 1.97. Thus it can be concluded that family support and self-esteem together have a significant effect on students' academic resilience (Hypothesis accepted)